2018
DOI: 10.4025/actascianimsci.v41i1.42552
|View full text |Cite
|
Sign up to set email alerts
|

Milk production and its relationship with milk composition, body and udder morphological traits in Bedouin goat reared under arid conditions

Abstract: This research aims to assess the performances of lactating Bedouin goat under arid conditions, focusing on the relationship of milk yield with body and udder morphology and growth traits. Fourteen goats and their kids were followed during early lactation (90 days post-partum). Mean daily milk yield was 0.56 kg. Milk fat, proteins, lactose, solids non-fat and minerals were respectively 34.9, 38.9, 48.8, 107 and 6.7 g L-1. Mean kids’ birth weight, adjusted body weight at 90 days of age and average daily gain wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
3
3
0
2
Order By: Relevance
“…Hasil penelitin ini menujukkan bahwa produksi susu kambing Peranakan Ettawa berikisar antara 0.68±0.01 sampai dengan 0.91±0.09 kg/hari (Tabel 4). Hasil tersebut lebih tinggi dibandingkan rata-rata produksi susu harian kambing perah Badui (Arab Saudia) yaitu sebesar 0,56 kg (Kouri et al, 2019), namun lebih rendah dibandingkan kambing Baladi (Arab Saudia), yaitu 1.11 -1.63 kg/hari (El-Tarabany et al, 2018). Perbedaan komposisi tersebut diduga karena perbedaan breed, musim dan pakan.…”
Section: Pengaruh Komposisi Ransum Terhadap Produksi Susuunclassified
See 1 more Smart Citation
“…Hasil penelitin ini menujukkan bahwa produksi susu kambing Peranakan Ettawa berikisar antara 0.68±0.01 sampai dengan 0.91±0.09 kg/hari (Tabel 4). Hasil tersebut lebih tinggi dibandingkan rata-rata produksi susu harian kambing perah Badui (Arab Saudia) yaitu sebesar 0,56 kg (Kouri et al, 2019), namun lebih rendah dibandingkan kambing Baladi (Arab Saudia), yaitu 1.11 -1.63 kg/hari (El-Tarabany et al, 2018). Perbedaan komposisi tersebut diduga karena perbedaan breed, musim dan pakan.…”
Section: Pengaruh Komposisi Ransum Terhadap Produksi Susuunclassified
“…Komposisi susu kambing perah Baladi (Arab Saudi), yaitu protein 3, 60-3,65%, lemak 3,27-3,30%, laktosa 3,85-4,09%, BK 10,99-11,29%, BKTL 7,74-7,80% (El-Tarabany et al, 2018). Komposisi susu kambing perah Badui (Arab Saudi), kandungan lemak susu, protein, laktosa, BKTL dan BK berturut-turut adalah 34,9; 38,9; 48,8; 10,7 dan 6,7 g per L (Kouri et al, 2019). Perbedaan komposisi tersebut diduga karena perbedaan breed, musim dan pakan.…”
Section: Pengaruh Komposisi Ransum Terhadap Komposisi Susuunclassified
“…According to Youssef et al (2014), body measurements of an animal is of importance to the farmers as it can be used for feeding, administering of medication, selection for breeding and management on the farm. Kouri et al (2019), reported that body weight and udder measurements play a significant role in milk yield. Based on the authors' knowledge, there is limited evidence on relationship between body measurements, udder measurements and milk yield of Holstein cows.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has conducted several studies on this local breed, focusing on its reproductive endocrine ecophysiology and pathophysiology [2][3][4][5][6] and endocrine and metabolic response in the Saharan environment [7,8]. Recently, the performance of lactating goats based on relationships between milk yield and udder morphological traits was investigated [9]. The low milk production has been demonstrated, since the average daily milk yield was 0.56 kg, reaching its peak (0.71 kg/day) at week 6 of lactation.…”
Section: Introductionmentioning
confidence: 99%